Safety Climate and Physical Workload of Nurses in Chengdu University Hospitals, People’s Republic of China - Chen , Cheng; Akkadechanunt, Thitinut; Chipakdee , Bunpitcha (Nursing Journal CMU, 2021)
Physical workload is the musculoskeletal load to the lower lumbar spine due to body posture and strenuous effort during work which affects the physical health of a person. This descriptive correlational research study aimed to explore safety climate, physical workload, and the relationship between safety climate and physical workload of nurses in Chengdu University Hospitals, People’s Republic of China. The sample was 304 nurses working in three university hospitals in Chengdu. Data collection was carried out from February to March 2018. The research instruments included the Safety Climate Measure (SCM) developed by Felknor (1997), the Index of Physical Workload (IPWL) developed by (Hollmann et al., 1999) and were translated into Chinese by the researcher without any modifications. The validity of the two instruments was confirmed by the developers. The Cronbach’s alpha of the SCM was .82, the 2-week test-retest reliability of the IPWL was .97. Descriptive statistics and Pearson’s correlation coefficient were used for data analysis. The results of this study showed that: The safety climate mean score as perceived by nurses was 3.44 (SD = 0.66). The nurse physical workload mean score was 27.78 (SD = 10.25). There was a statistically moderate negative relationship between safety climate and physical workload (r = -.32, p < .001). The findings of this study provide basic information for nursing administrators to develop strategies to maintain a safety climate in order to decrease the physical workload of nurses in Chengdu University hospitals in the People’s Republic of China.